Pengetahuan guru Pendidikan Islam prasekolah dalam rangka pembangunan tamadun ummah - Mohamed, Sofiah (Skudai Johor, 2016)
This aim of the research to explore the knowledge of Islamic education preschool teacher’s about the development of preschool children and to determine the implementation of that knowledge in teaching and learning. This study is a qualitative case study approach with the main instrument is observation methods. These observation data triangulate with interviews and document analysis data. Selection of study participants using purposeful sampling aimed those who experienced the pre-school teaching for more than three years, have participated in courses and training of the Ministry of Education (MOE) and volunteered to participate in the study. The results found that teachers who participated in the study had a source of knowledge about the development of preschool children through courses, training and experience. Study participants have been practicing existing knowledge in the implementation of teaching and learning in the classroom. Teachers can also perform knowledge coincide with the objectives of preschool education. Insights data generating Preschool Teacher’s Knowledge Model proposed to the District Education Office (PPD), the State Education Department (JPN), Ministry of Education (MOE), the private sector, teachers, and parents in order to attempt the education of children in preschool. Keywords: Islamic education teacher; ummah civilization; preschool; child development.